German "Soft power" Policies in the Muslim World - L. R. Rustamova (MGIMO University Press, 2015)
In recent years, a number of foreign policy concepts declared the importance of using the instruments of "soft power" to promote the national interests of a country. Soft power is the ability through political values, culture and foreign policy to influence others by forming attractiveness [18]. Germany is generally recognized as the leader in the resources of "soft power." The article discusses what kind of resources are deployed by Germany to increase its "soft power" in the Muslim direction of foreign policy. The Muslim world has its own specifics, which complicate the use of instruments of "soft power." Countries with large Muslim population are difficult to influence, as they differ from Europe in the civilizational respect, have their own customs and traditions which they strictly follow because of the nature of Muslim religion. The author notes that in the Muslim direction of foreign policy the problem for Germany lies in the fact that the formation of its attractiveness resulted in a significant flow of immigration of Muslims in the country. A part of immigrant Muslims tries to live isolated from European society, professes radical currents ofIslam and participates in military conflicts abroad, participation in which in the role of active player is ruled out by Germany. Failure to integrate them into German society and the lack of progress in the formation of its positive image in the Muslim countries resulted, on the one hand, in the split of German society, on the other hand, in the threat of absorption by foreign civilization, as it is observed now in Germany the presence of "soft power" of Muslim countries, which use its former and current citizens to influence German political course. The article was written within the constructivist methodology, which consider the "soft power" as a way of construction of social reality with the use of tangible and intangible resources for the formation of an attractive image of Germany in world politics.